Metachondromatosis without Enchondromas: A Case Report and Review of the Literature. Issue 2 (27th April 2016) - Kanaya, Kohei; Ishikawa, Aki; Yaoita, Masako; Niihori, Tetsuya; Aoki, Yoko; Iba, Kousuke; Yamashita, Toshihiko
Abstract : Case: A nine-year-old boy had multiple osteochondromas in the hands, feet, and tibiae, many of which pointed toward the adjacent joint. Although several were treated surgically, others resolved spontaneously. A heterozygous mutation in the PTPN11 gene was identified by genetic analysis of peripheral blood, so the patient was diagnosed with metachondromatosis despite the absence of enchondromatous lesions. Conclusion: To the best of our knowledge, this is the first reported case of a patient with metachondromatosis without any enchondromatous lesions.